Influence of Sugar, Ammonium Nitrate and Plant Growth Regulators on in vitro Flowering of Celosia argentea var. cristata - Krupa-Ma kiewicz Marcelina; Mg osiek Oktawia (Journal of Basic & Applied Sciences, 2016)
In vitro flowering is considered to be a complex process regulated by a vast of environmental and genetic factors. The present study describes the influence of sugar, ammonium nitrate and plant growth regulators on in vitroflowering from nodal explants of Celosia argentea var. cristata cultured for 6 weeks on basal MS medium under aseptic and light conditions. The addition to MS medium different concentrations of sucrose or ammonium nitrate did not influence on morphogenesis of Celosia plants. Among the plant growth regulators tested, supplementation with 1.0 mg/l KIN induced maximum number of new shoots (2.52). Flowering occurred on 100% of in vitro shoots cultured on modify MS medium supplemented with 16.50 and 8.25 g/l of NH4NO3 after 40 days.